MODELLING OF THE LONG RUN IMPACT OF EXPORTS AND IMPORTS ON FOREIGN EXCHANGE RESERVE INFLOW IN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
This study examined the long run relationship and causality among exports and imports data as explanatory variables to foreign reserves inflow into the Nigeria’s economy from January 2008 to December 2018 using Autoregressive Distributed Lag (ARDL) Bounds test approach to cointegration. The secondary data was obtained from the Central Bank of Nigeria. A unit root test of stationarity of the series returned all three series to be I(1) stationary. Bounds test result shows that there is cointegration among the variables specified in the model. The optimal lags specification returned ARDL (3, 0, 0) as overall best fitting model for monthly inflow of Foreign reserves. The speed of adjustment to long run equilibrium of 22.15% is significant to minimized distortions in the long run. The causality result highlights the crucial role exports trade plays in the accumulation of foreign reserves. Diagnostics checks on the model provided no significant evidence of serial correlation or presence of instability in the estimated coefficients at 5% significance level. The study recommends that Policy Makers should ensure definite steps are taken to diversify the country’s export trade so as to spur external reserves inflow, this will give the Country worthiness in the international market and leverage in times of economic crises thereby stabilising the economy, a stable economy will attract foreign direct investments which will further boost infrastructural development and in a long run a better living standard of the citizenry.
Keywords: ARDL, Cointegration, Causality, Stationarity, Bounds test